2020
DOI: 10.1016/j.ahj.2019.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Average daily ischemic versus bleeding risk in patients with ACS undergoing PCI: Insights from the BleeMACS and RENAMI registries

Abstract: Introduction. The risk of recurrent ischemia and bleeding after percutaneous coronary intervention (PCI) for acute coronary syndrome (ACS) may vary during the firstyear of follow-up according to clinical presentation, medical and interventional strategies.Methods. BleeMACS and Renami are two multicenter registries enrolling patients with ACS treated with PCI and clopidogrel, prasugrel or ticagrelor. The average daily ischemic and bleeding risks (ADIR and ADBR) in the first year after PCI were the primary endpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…DAPT with potent P2Y12 inhibitors are the keystone of ACS treatment in the general adult population, as previous evidence demonstrated the benefit of this strategy in decreasing cardiovascular mortality, recurrent MI or coronary revascularization after ACS due to the reduction of the thrombotic risk [14]. However, such benefit comes invariably at expense of an increased risk of bleeding events [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…DAPT with potent P2Y12 inhibitors are the keystone of ACS treatment in the general adult population, as previous evidence demonstrated the benefit of this strategy in decreasing cardiovascular mortality, recurrent MI or coronary revascularization after ACS due to the reduction of the thrombotic risk [14]. However, such benefit comes invariably at expense of an increased risk of bleeding events [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…There were insufficient data to assess the potential benefit of a strategy of selective or bailout aspiration thrombectomy (Class IIb, LOE C-LD), defined as unplanned thrombectomy performed due to unsatisfactory initial result or procedural complication, analogous to the definition of "bailout" glycoprotein IIb/IIIa use [19]. Recent studies have demonstrated the benefit of complete revascularization [20,21], nevertheless, at the time this study was conducted, we only performed culprit-only PCI. Hence, this issue was not expected to greatly influence the analysis and its result.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these regimens may substantially increase bleeding risk, especially during the early TAT period [2,8]. Recent studies have demonstrated that both average daily bleeding rates and average daily ischemic rates are highest during the first month immediately after PCI, followed by a gentle downward curve [17,18]. These high bleeding rate and ischemic rate in the first month after the PCI is estimated to be even higher in AF patients undergoing PCI.…”
Section: Pitfalls Of Conventional Antithrombotic Therapymentioning
confidence: 99%